Effects of alpha-ketoisocaproate in oxidative stress-induced C2C12 myotubes via inhibition of p38 MAPK and ERK1/2 - Pooreum Lim; Sang Woo Woo; Jihye Han; Young Lim Lee; Jae Ho Shim; Hyeon Soo Kim (Biochemistry and Biophysics Reports)
Sarcopenia is an age-related muscle atrophy characterized by decreased muscle mass and function. However, potential treatments to alleviate sarcopenia remain limited. In this study, we investigated the effects of α-ketoisocaproate (KIC) on C2C12 differentiation and reactive oxygen species (ROS)-induced atrophy in C2C12 myotubes. We demonstrated that KIC upregulates the expression of myogenic differentiation factors, including myoblast determination protein 1 (MyoD) and myogenin (MyoG), during C2C12 differentiation. Additionally, KIC enhanced the expression of myosin heavy chain (MHC) isoforms MHC1, MHC2b, and MHC2x in C2C12 myotubes. KIC suppressed the decreased MyoG expression and the increase in the muscle atrophy-related factor, muscle atrophy F-box (MAFbx), in ROS-induced C2C12 myotubes. In addition, it restored the reduced expression of MHC and the diameter of C2C12 myotubes. We showed that KIC alleviated muscle atrophy by inhibiting mitogen-activated protein kinase (MAPK) signaling pathways, such as p38 MAPK and extracellular signal-regulated kinase 1/2 (ERK1/2). These findings suggest that KIC may serve as a potential therapeutic agent for ameliorating sarcopenia by inhibiting MAPK signaling in ROS-induced skeletal muscle cells.